Life status and demographic characteristics of IAPES’ members during the COVID-19 pandemic - Argarin, Jesus; Cruz, Lucia B Dela (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2022)
This study on the life status of IAPES members based on identified conditions and their demographic characteristics during the COVID-19 pandemic was conducted to provide an updated profile of the members of the International Association of Physical Education and Sports. The objectives of the study is to collect data and information based on the following: (i) demographic characteristics of selected IAPES members as to their country of origin, age, sex, civil status, educational attainment, length of service as PE teacher, length of service in their current institution, and the type of institution they are employed; (ii) the current life status of selected IAPES members in terms of psychological, physical, financial, work/professional, and sociocultural conditions; (iii) presence of significant relationships on the current life status when grouped according to their demographic characteristics; (iv) how the selected IAPES’ members describe their greatest attributes that have helped them cope with the COVID-19 pandemic; and, (v) what other matters have been bothering the selected IAPES’ members in relation to the prevalence of the pandemic. The study used mixed methods of research, the quantitative (descriptive-correlational) and qualitative (descriptive-exploratory) methods. Moreover, the study utilized purposive-convenient sampling techniques in the selection of 246 IAPES’ members from the Philippines, India, Malaysia, Bangladesh, Egypt, Ethiopia, Pakistan, Iran, Thailand, and United States. Results show that respondents’ life status based on the cited conditions have significant relationships when grouped according to the respondents’ country of origin, sex (except for the physical condition), and educational attainment, while there are no significant relationships based on their age, civil status (except for physical and work/professional conditions), length of service as PE teacher, length of service in the current institution, and type of institution. Moreover, there were 5 greatest attributes in coping with the COVID-19 pandemic identified by the respondents, resilience, attitude of maintaining good physical condition, seeking for families’ and friends’ support in times of crisis, volunteerism, and faith in God. Other matters bothering the respondents related to COVID-19 pandemic are financial stability, family’s safety, learning more about mental health, their students’ learning conditions, and the lack of initiatives from the authorities in battling the COVID-19 pandemic.